2002
DOI: 10.1111/j.1471-0528.2002.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood sampling at delivery: do we need to always collect from both vessels?

Abstract: The literature suggests that up to 19% of umbilical cord blood samples are invalid. Accordingly, it has been proposed that blood should be universally collected from both vessels. We prospectively collected paired arterial and venous blood to examine whether our centre, where staff were experienced in single vessel collection, was more accurate. Of 289 paired samples, 53 (18.3%) were considered invalid. Despite this significant error rate, we propose that routinely, only arterial sampling is needed and that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 6 publications
1
12
2
Order By: Relevance
“…Historically, the proportion of samples declared nonvalid varies from 5 to 37% of the population evaluated. 3,7,11,13,[21][22][23][24][25][26][27][28] Apart from the inability to obtain an arterial and/or venous sample, the most common postulated mistake is the inadvertent switching of umbilical arterial and venous samples or sampling the same umbilical vessel twice (typically the umbilical vein). Early studies of UCBG values relied on the skill of the midwifery and medical staff members' sampling technique, and typically only reported values from a single umbilical vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the proportion of samples declared nonvalid varies from 5 to 37% of the population evaluated. 3,7,11,13,[21][22][23][24][25][26][27][28] Apart from the inability to obtain an arterial and/or venous sample, the most common postulated mistake is the inadvertent switching of umbilical arterial and venous samples or sampling the same umbilical vessel twice (typically the umbilical vein). Early studies of UCBG values relied on the skill of the midwifery and medical staff members' sampling technique, and typically only reported values from a single umbilical vessel.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of support for umbilical cord blood gas (UCBG) analysis to be undertaken on all deliveries to provide an objective marker of neonatal biochemical status at delivery 1-6 that in turn can identify neonates that have been exposed to perinatal asphyxial insults. Although some authors have advocated sampling only the umbilical artery, 7 the majority of authors and professional societies strongly advocate obtaining and analysing samples from both the umbilical artery and vein [8][9][10][11][12] to ensure the biological validity of the blood gas values obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the previous report was of only 17 pregnancies compared with 141 here. In addition, the arterial samples in the current study were validated according to agreed criteria, 10,11 whereas this was not undertaken in the prior report. Accordingly, we believe that the current data are more likely to be truly representative, and therefore that umbilical artery activin A is not likely to be useful as a marker of fetoplacental oxygenation at the time of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…vein instead of artery). 10,11 Therefore, only validated samples, using previously proposed criteria, 10,11 were utilised in this study. Briefly, samples were considered valid only when umbilical vein pH was > 0.02 and CO 2 < À4 mmHg, relative to the artery.…”
Section: Methodsmentioning
confidence: 99%
“…8 Previous studies have shown that universal UCBGA can reduce the proportion of hypoxic children over time, and a cost-effectiveness analysis showed that changing the recommendation from selective to universal UCBGA reduced costs, mainly through a reduction in admissions to special care nursery for children with birthweight >2499 g. 8,9 In settings where universal measurement of UCBGA is recommended, mostly single hospitals or administrative regions, the proportion of births with UCBGA varies from 49% in Alabama, USA, to 81% in Victoria, Australia, with UCBGA still missing in a substantial proportion of births. 5,10,11 Prior to 2009 policy in Danish maternity wards varied from no UCBGA to UCBGA in cases with suspicion of hypoxia. In 2009 the Danish Society of Obstetrics and Gynecology introduced a national recommendation of universal measurement of umbilical cord pH (UC-pH) as part of UCBGA.…”
Section: Introductionmentioning
confidence: 99%